Helicobacter pylori infection and apolipoprotein B/apolipoprotein A1 ratio: a cross-sectional study - Liu, Chao; Zhu, Xuping; Pu, Jiale; Zou, Zhuoqun; Zhou, Lu; Zhu, Xiaowei (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundHelicobacter pylori (HP) infection is one of the most common chronic infections worldwide, closely related to various gastrointestinal diseases and metabolic disorders. In recent years, the relationship between HP infection and abnormal glucose and lipid metabolism has received significant attention, although its specific mechanisms remain unclear. This study aims to explore the association between HP infection and lipid metabolism abnormalities, particularly the role of the apolipoprotein B/A1 (ApoB/ApoA1) ratio.MethodsThis cross-sectional study retrospectively analyzed data from 9,218 patients who underwent physical examinations at Shanghai Health and Medical Center in 2022. HP infection status was determined using the carbon-13 breath test, and clinical data, biochemical indicators, and lipid metabolism-related data were collected. Multiple regression analysis was employed to investigate the relationship between HP infection and the ApoB/ApoA1 ratio.ResultsPatients in the HP-positive group were older and had a higher proportion of males. Their body mass index (BMI), blood pressure, γ-glutamyl transpeptidase (γ-GT), total cholesterol (TC), fasting blood glucose (FBG), Creatinine and White blood Cell were significantly higher than those in the HP-negative group. The HP-positive group exhibited a higher prevalence of underlying diseases (e.g., hypertension, diabetes, coronary heart disease) and significant abnormalities in glucose and lipid metabolism, uric acid, high-sensitivity C-reactive protein (hs-CRP), and other indicators. The ApoB/ApoA1 ratio was significantly elevated in the HP-positive group and was not influenced by gender. Multiple regression analysis revealed that the ApoB/ApoA1 ratio is an independent risk factor for HP infection.ConclusionHP infection is closely associated with abnormal lipid metabolism, and the ApoB/ApoA1 ratio is an independent risk factor for HP infection, demonstrating significant advantages over other lipid indicators. This large-scale study highlights a significant association between HP infection and an elevated ApoB/ApoA1 ratio. The findings suggest that HP may contribute to cardiovascular risk via dyslipidemia, with the ApoB/ApoA1 ratio serving as a potential biomarker. Further research should explore whether HP eradication could mitigate these metabolic disturbances.